Pemilihan Rute Tol dan Non-Tol Menggunakan Metode Stated Preference: Studi Kasus Koridor Malang-Surabaya - Sari, Chalsi Mala; Kore, Desri M. Hale; Devedo, M. Gaharu Dida; Tristanto, Kartika; Supriyanto, Muhammad Ibadurrahman Arrasyid (Universitas Batanghari Jambi, 2025)
The development of toll roads in the Malang-Surabaya corridor has transformed travel patterns and provided route alternatives for road users. This study analyzes factors influencing route choice decisions between toll and non-toll roads using the Stated Preference (SP) method. A survey was conducted on 103 respondents using experimental design involving three main attributes: travel cost difference (IDR 15,000-45,000), travel time difference (15-45 minutes), and travel distance difference (3-9 km). The analysis results show that travel cost and travel time significantly influence route choice with excellent model fit (R² = 0.724), while travel distance has minimal effect (R² = 0.089). The utility model produces a Value of Time of IDR 44,045 per hour with preference equilibrium points at cost difference of IDR 22,340 or time difference of 18.9 minutes. Segmentation analysis reveals significant preference heterogeneity where private car users show 66% toll preference compared to motorcycle users at only 14%. Business travelers demonstrate higher toll preference (36%) compared to non-business travelers (64%). The model achieves 95.7% prediction accuracy and can be applied for dynamic pricing strategies, traffic distribution forecasting, and optimal toll tariff policy evaluation for efficient transportation planning in similar corridors.